Building and Standardizing a Motor Awareness Scale in Artistic Gymnastics for Students - Yaser, Zaid Sami (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The research aimed to construct and standardize a Motor Awareness Scale for first-year students in the College of Physical Education and Sports Sciences – University of Kufa. The researcher used the descriptive method in the form of scale construction. The research population consisted of (85) students, and a random sample of (60) students was selected for scale construction and application. The scale was developed according to six main domains: sensory–bodily perception, spatial motor perception, balance sensation and body control, muscular effort awareness, temporal awareness of movement, and motor attention and focus. The final version of the scale consisted of (36) items. The results showed that the sample possessed an average level of motor awareness. Norms and levels for the scale were also established, making it a scientifically valid tool for future research.